Baricitinib restrains the immune dysregulation in patients with severe COVID-19 - Bronte, Vincenzo; Ugel, Stefano; Tinazzi, Elisa; Vella, Antonio; De Sanctis, Francesco; Canè, Stefania; Batani, Veronica; Trovato, Rosalinda; Fiore, Alessandra; Petrova, Varvara; Hofer, Francesca; Barouni, Roza Maria; et al. (The Journal of Clinical Investigation, 2020)
BACKGROUND Patients with coronavirus disease 2019 (COVID-19) develop pneumonia generally associated with lymphopenia and a severe inflammatory response due to uncontrolled cytokine release. These mediators are transcriptionally regulated by the JAK/STAT signaling pathways, which can be disabled by small molecules.METHODS We treated a group of patients (n = 20) with baricitinib according to an off-label use of the drug. The study was designed as an observational, longitudinal trial and approved by the local ethics committee. The patients were treated with 4 mg baricitinib twice daily for 2 days, followed by 4 mg per day for the remaining 7 days. Changes in the immune phenotype and expression of phosphorylated STAT3 (p-STAT3) in blood cells were evaluated and correlated with serum-derived cytokine levels and antibodies against severe acute respiratory syndrome–coronavirus 2 (anti–SARS-CoV-2). In a single treated patient, we also evaluated the alteration of myeloid cell functional activity.RESULTS We provide evidence that patients treated with baricitinib had a marked reduction in serum levels of IL-6, IL-1β, and TNF-α, a rapid recovery of circulating T and B cell frequencies, and increased antibody production against the SARS-CoV-2 spike protein, all of which were clinically associated with a reduction in the need for oxygen therapy and a progressive increase in the P/F (PaO2, oxygen partial pressure/FiO2, fraction of inspired oxygen) ratio.CONCLUSION These data suggest that baricitinib prevented the progression to a severe, extreme form of the viral disease by modulating the patients’ immune landscape and that these changes were associated with a safer, more favorable clinical outcome for patients with COVID-19 pneumonia.TRIAL REGISTRATION ClinicalTrials.gov NCT04438629.FUNDING This work was supported by the Fondazione Cariverona (ENACT Project) and the Fondazione TIM.